Pengaruh Karakteristik Komite Audit dan Kualitas Audit terhadap Penyajian Kembali Laporan Keuangan - Steven Lois; Hansen Suardi; Sany Sany (Business Accounting Review, 2021)
This study's objective is to look at the impact of audit committee characteristics and thesize of the audit firm on the restatement of financial statements of financial sector companies listedon the Indonesia Stock Exchange for the period of 2016 to 2020. Measurement of audit committeecharacteristics is proxied by indicators of audit committee independence, audit committee size,number of audit committee meetings, audit committee expertise, and size of audit firm. This studyuses firm size and firm performance as control variabels. Meanwhile, the restatement of financialstatements is measured using a dummy variabel, where